![\begin{gathered} (5x)/(6)+(y)/(3)=(4)/(3) \\ (2x)/(3)-(y)/(2)=(11)/(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rxf9blh2ooj5wh8uxi5y0c33873svred0f.png)
to solve this,
Step 1
the purpose of this method is eliminate a variable by adding the two equations, to do this, you need to be sure that the add will make that variable disappear.
Let's see y
![\begin{gathered} (y)/(3) \\ \text{and} \\ -(y)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/87ipz6lf131yp4rvesih182xmidkr1v30q.png)
to eliminate y make
![\begin{gathered} multiply\text{ the first equation }by\text{ }(1)/(2) \\ \\ (5x)/(6)+(y)/(3)=(4)/(3)\text{ by }(1)/(2) \\ (1)/(2)\cdot(5x)/(6)+(1)/(2)\cdot(y)/(3)=(1)/(2)\cdot(4)/(3) \\ (5x)/(12)+(y)/(6)=(2)/(3)\text{ equation (3)} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fnr9so5hzamnufeheimapint4ckw9p7u7x.png)
Now, multiply the second equation by 1/3
![\begin{gathered} (2x)/(3)-(y)/(2)=(11)/(6)\text{ by }(1)/(3) \\ (1)/(3)\cdot(2x)/(3)-(1)/(3)\cdot(y)/(2)=(1)/(3)\cdot(11)/(6) \\ (2x)/(9)-(y)/(6)=(11)/(18)\text{ equation (4)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pwm85hpk1g90undiuyspa0ymjqa7cb3rca.png)
Now, add equations 3 and 4
![\begin{gathered} (5x)/(12)+(y)/(6)=(2)/(3) \\ (2x)/(9)-(y)/(6)=(11)/(18) \\ x((5)/(12)+(2)/(9))=(2)/(3)+(11)/(18) \\ x((23)/(36))=(23)/(18) \\ x=(23\cdot18)/(36\cdot23) \\ x=(414)/(828) \\ \\ x=(1)/(2) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c0ihn6uhcfaq2b6erpwnj2idf8xrg3m77i.png)
Now, with this value of x, find y, replacing in the equation 1 or 2
![\begin{gathered} (2x)/(3)-(y)/(2)=(11)/(6) \\ (2((1)/(2)))/(3)-(y)/(2)=(11)/(6) \\ (1)/(3)-(y)/(2)=(11)/(6) \\ -(y)/(2)=(11)/(6)-(1)/(3) \\ -(y)/(2)=(3)/(2) \\ y=(3\cdot-2)/(2) \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/28xk7t1wz14fjgy6771ianfhskxh1w44ts.png)
so, the solution is x=0.5 and y =-3
I really hope this helps